Pengaruh Kualitas Produk, E-Wom dan Jaringan Terhadap Keputusan Konsumen Membeli Produk Kesehatan di PT. Melia Sehat Sejahtera Medan - Indra Bayu Siregar; Tukimin Lubis; Nur’ain Harahap; Munawaroh Munawaroh (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Several factors influence consumer purchasing decisions at PT Melia Sehat Sejahtera Medan including product quality, e-WOM and network. This research aims to find out how much influence product quality, e-WOM and network have on consumer purchasing decisions at PT Melia Sehat Sejahtera Medan. The research method used in this research is quantitative descriptive research, the sampling technique in this research is using the Slovin Formula, where a population of 120 is then a sample of 55 people. The data collection techniques used were observation, questionnaires. The data analysis technique used is the multiple linear regression test. Based on the research results, there is a partial influence of product quality variables on consumer purchasing decisions. The e-wom variable influences consumer purchasing decisions. Network variables influence consumer purchasing decisions. Simultaneously, product quality, e-WOM and network variables jointly influence consumer purchasing decisions at PT Melia Sehat Sejahtera Medan.